The Role of Interest and Belief in Increasing Loyalty Among Users of Sharia E-Money in Makassar City - Jamaluddin; Hastuti; Ayesha Smitha; Anwar Enre; Auliah Alwi (Bulletin of Community Engagement, 2026)
This research investigates the factors influencing the loyalty of Sharia e-money users in Makassar City, Indonesia, amidst the rapid development of digital payment systems, including sharia-based e-money. The study emphasizes the importance of Trust and Interest in driving user loyalty. A quantitative approach with a causal-associative design was adopted, involving 100 randomly selected respondents from a population of 1.5 million. Data were collected through a closed questionnaire and analyzed using Structural Equation Modelling (SEM) with SmartPLS. The results revealed that both Trust (β = 0.199; p = 0.010) and Interest (β = 0.670; p < 0.001) significantly influenced loyalty, with Interest emerging as the dominant factor. The research model accounted for 69.5% of the variation in loyalty (R² = 0.695), and the instrument met the required validity and reliability criteria. The study concludes that boosting Interest through effective promotion, innovative services, and a strong Sharia image is more influential in fostering loyalty compared to solely focusing on Trust, though both factors remain crucial. This research contributes valuable insights to Sharia e-money service providers and regulators, offering strategic guidance for the development of policies aimed at enhancing user loyalty. Furthermore, it enriches the Sharia digital finance literature, particularly in the context of Makassar, which presents unique market characteristics.